TRENDS AND ATTITUDES TOWARD ONCOPLASTICS TRAINING IN MASTOLOGY IN BRAZIL - Urban, Cícero; Gazoto Júnior, Orivaldo; Pires, Douglas Miranda; Garcia, Guilherme Novita; Paulinelli, Regis Resende; Amoroso, Vanessa; Freitas Júnior, Ruffo (Mastology, 2017)
Introduction: There is a growing interest in, and an increasing demand for, oncoplastic (OP) and reconstructive surgery training by breast surgeons. However, until now there has been a lack of a specific model for training in this field in most countries and no data with respect to learning curves. Mastology has been a medical specialty in Brazil since 1978. It is fully dedicated to studying, preventing, diagnosing, and managing all diseases of the breast. Incorporation of OP and reconstructive surgery in Mastology presents a number of challenges, and there are some controversial issues to overcome. Objective: The purpose of this study, therefore, was to analyze how OP and reconstructive techniques are being incorporated into surgical training in Mastology in Brazil. Methods: A specific survey was designed to cover all surgical residents who concluded their regular program in Mastology in Brazil in 2015 and 2016. Results: One hundred twenty-four residents from 49 breast units were included, with the majority having their training for all 2 years of their residence, as recommended by the Brazilian Society of Mastology. In addition, most of the respondents were able to perform partial breast reconstructions and reconstructions using expanders and implants, but 20% of them had a lack of specific training in these techniques. Conclusion: As adequate local control of disease and quality of life are related to surgical decisions, it is expected that breast surgeons expand their limits and responsibilities in order improve the reality of most breast cancer patients.